Presence and Germination of the Probiotic Bacillus subtilis DE111® in the Human Small Intestinal Tract: A Randomized, Crossover, Double-Blind, and Placebo-Controlled Study - Colom, Joan; Freitas, Daniela; Simon, Annie; Brodkorb, Andre; Buckley, Martin; Deaton, John; Winger, Alison M. (Frontiers in Microbiology, 2021)
Spore-based probiotics offer important advantages over other probiotics as they can survive the harsh gastric conditions of the stomach and bile salts in the small intestine, ultimately germinating in the digestive tract. A novel clinical trial in 11 ileostomy participants was conducted to directly investigate the presence and germination of the probiotic strain Bacillus subtilis DE111® in the small intestine. Three hours following ingestion of DE111®, B. subtilis spores (6.4 × 104 ± 1.3 × 105 CFU/g effluent dry weight) and vegetative cells (4.7 × 104 ± 1.1 × 105 CFU/g effluent dry weight) began to appear in the ileum effluent. Six hours after ingestion, spore concentration increased to 9.7 × 107 ± 8.1 × 107 CFU/g and remained constant to the final timepoint of 8 hours. Vegetative cells reached a concentration of 7.3 × 107 ± 1.4 × 108 CFU/g at 7 hours following ingestion. These results reveal orally ingested B. subtilis DE111® spores are able to remain viable during transit through the stomach and germinate in the small intestine of humans within 3 hours of ingestion.